ESCRTing endoplasmic reticulum to microautophagic degradation. Issue 4 (2nd April 2020) - Schäfer, Jasmin A.; Schuck, Sebastian
ABSTRACT: Changing conditions necessitate cellular adaptation, which frequently entails adjustment of organelle size and shape. The endoplasmic reticulum (ER) is an organelle of exceptional morphological plasticity. In budding yeast, ER stress triggers the de novo formation of ER subdomains called ER whorls. These whorls are selectively degraded by a poorly defined type of microautophagy. We recently showed that ESCRT proteins are essential for microautophagic uptake of ER whorls into lysosomes, likely by mediating the final scission of the lysosomal membrane. Furthermore, ER-selective microautophagy acts in parallel with ER-selective macroautophagy. The molecular machineries for these two types of autophagy are distinct and their contributions to ER turnover vary according to conditions, suggesting that they serve different functions. Our study provides evidence for a direct role of ESCRTs in microautophagy and extends our understanding of how autophagy promotes organelle homeostasis.